Novice Teachers in Private and Public Primary Schools in Azerbaijan: Exploring the Experiences - Najafova, Aytaj (ADA University, 2024)
The purpose of this study is to explore the experiences of novice teachers and analyze how they might affect their career in primary public/private schools in Azerbaijan. This study focused on experiences of novice teachers related to school culture, relationship with colleagues and administration, professional development programs, and challenges and how these experiences affect their career. Semi structured interviews were conducted with four novice teachers (2 private and 2 public schools) from both private and public schools for this study. Results of the study demonstrated that how school culture, relationship with colleagues and administrations, and professional development programs impact on novice teachers’ growth and development as professionals. The supportive school culture and positive relationship withing the school greatly influence novice teachers’ commitment to their workplace. The implementation of professional development programs made novice teachers more qualified, equipped, and confident in the classroom.
Keywords: Novice teachers -- Professional development -- Career development.; Teachers -- Professional development -- School culture; Teacher-student relationships -- School culture -- Professional growth; School culture -- Novice teachers -- Career impact.; Public schools -- Teacher development -- Azerbaijan; Azerbaijan -- Education -- Teachers; Education